Coupled coincidence point theorems for new types of mixed monotone multivalued mappings in partially ordered metric spaces - Klanarong C. (2014)
We introduce and study new types of mixed monotone multivalued mappings in partially ordered complete metric spaces. We give relationships between those two types of mappings and prove their coupled fixed point and coupled common fixed point theorems in partially ordered complete metric spaces. Some examples of each type of mappings satisfying the conditions of the main theorems are also given. Our main result includes several recent developments in fixed point theory of mixed monotone multivalued mappings. © 2013 Chalongchai Klanarong and Suthep Suantai.